2020
DOI: 10.4317/medoral.23335
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical analysis of cancer-associated fibroblasts and podoplanin in head and neck cancer

Abstract: Background: To immunohistochemically evaluate the association between the presence of cancer-associated fibroblasts (CAFs) and the tumour expression of podoplanin (PDPN) in head and neck squamous cell carcinoma (HNSCC) and their association with clinicopathological variables. Material and Methods: A tissue microarray (TMA) with biopsy sections from patients diagnosed with HNSCC was stained with antibodies against the CAFs marker, α-smooth muscle actin (α-SMA), and PDPN. We subsequently evaluated their expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
(43 reference statements)
0
10
0
Order By: Relevance
“…Parkinson, unpublished data). This concept is supported indirectly by the observation that α-smooth muscle actin expression (α-SMA, a marker of fibroblast activation) can be homogeneous or focal within OSCC tissues 15 . It has been shown previously that keratinocytes from GU-OSCCs induced senescence in fibroblasts via the production of ROS and this mechanism is dependent upon CAF-derived TGF-β1 16 .…”
Section: Introductionmentioning
confidence: 98%
“…Parkinson, unpublished data). This concept is supported indirectly by the observation that α-smooth muscle actin expression (α-SMA, a marker of fibroblast activation) can be homogeneous or focal within OSCC tissues 15 . It has been shown previously that keratinocytes from GU-OSCCs induced senescence in fibroblasts via the production of ROS and this mechanism is dependent upon CAF-derived TGF-β1 16 .…”
Section: Introductionmentioning
confidence: 98%
“…Twelve studies (897 patients) used samples from oral squamous cell carcinoma, with one of the twelve limiting their analysis to advanced (T3 or T4) oral samples (31). The remaining study evaluated 29 patients with various Head and Neck SCC primary sites including sinonasal, oral, and laryngeal (34). Six studies reported clinical stage according to guidelines from the Union for International Cancer Control and American Joint Committee on Cancer, while three studies reported TNM stage without specifying which staging guidelines were utilized.…”
Section: Resultsmentioning
confidence: 99%
“…Articles found from the search were selected for further analysis according to the following criteria: (1) English language; (2) human subjects; (3) squamous cell carcinoma of the head and neck; (4) measurement of CAFs using either alpha-smooth muscle actin (a-SMA) or Fibroblast Activation Protein (FAP) via immunohistochemistry; (5) available data on one or more of the following clinical and pathologic characteristics: T stage, N stage, clinical stage, vascular invasion, perineural invasion, Ki67, differentiation, and recurrence. After identification, screening, and determination of eligibility, 13 studies were included in the meta-analysis ( Figure 1) (22,24,25,(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). Based on the methods of the selected studies, as well as to facilitate analysis with dichotomous variables, the pathologic markers were grouped in the following manner: advanced T stage included T3 or T4 lesions; nodal positivity included all tumors staged N1-3; clinical stages of III and IV were classified as advanced; poor differentiation was applied to only those samples truly graded as poor; vascular invasion was deemed to be positive or not positive; Ki67 staining was graded as high or low based on a cutoff percentage of positive staining (range: 26-32.4%); perineural invasion was noted to be present or not present; recurrence was either present or not present.…”
Section: Methodsmentioning
confidence: 99%
“…CAFs were established as one of the major players within the TME involved in the progression of HNCs [ 28 ]. Herein, we examined the effects of HNC0014 on CAFs by culturing NFs in the presence of Exo sp .…”
Section: Resultsmentioning
confidence: 99%
“…Cancer-associated fibroblasts (CAFs) represent one of the most influential stromal cell populations within the TME, which are involved in the progression of HNSCC [ 28 ], and targeting them increases chemosensitivity [ 40 ]. In agreement with previous studies [ 41 ], we reported that Exo sp -transformed CAFs expressed higher levels of the specific fibroblast markers FAP, α-SMA, and vimentin, which exhibited higher secretion of HGF compared to their NF counterparts.…”
Section: Discussionmentioning
confidence: 99%